Associations between intra-arrest blood glucose level and outcomes of adult in-hospital cardiac arrest: A 10-year retrospective cohort study. (1st January 2020) - Wang, Chih-Hung; Chang, Wei-Tien; Huang, Chien-Hua; Tsai, Min-Shan; Chou, Eric; Yu, Ping-Hsun; Wu, Yen-Wen; Chen, Wen-Jone
Abstract: Aim: We attempted to examine the association between intra-arrest blood glucose (BG) level and outcomes of in-hospital cardiac arrest (IHCA). The interaction between diabetes mellitus (DM) and BG level as well as between dextrose administration and BG level were investigated. Methods: This single-centred retrospective study reviewed IHCA patients between 2006 and 2015. Patients with measured intra-arrest BG levels were included. Multivariable logistic regression analyses were conducted. Generalised additive models were used to identify appropriate cut-off points for continuous variables. Interactions between independent variables were assessed during the model-fitting process. Results: Among the 580 included patients, 34 (5.9%) achieved neurologically intact survival. There were 197 DM patients (34.0%). The mean intra-arrest BG level was 191.5 mg/dl, with 57 patients (9.8%) experiencing hypoglycaemia (BG level ≤ 70 mg/dl). A total of 165 patients (28.4%) received a dextrose injection. An intra-arrest BG level ≤ 150 mg/dl was inversely associated with favourable neurological outcomes at hospital discharge (odds ratio [OR]: 0.28, 95% confidence interval [CI]: 0.11–0.73; p-value = 0.01). In analyses of interactions, non-DM × BG level ≤ 168 mg/dl was inversely associated with favourable neurological outcomes (OR: 0.30, 95% CI: 0.11–0.80; p-value = 0.02). There were no significant interactions between BG level and dextrose administration. Conclusion: IHCA patients with intra-arrest BG level ≤ 150 mg/dl had worse neurological recovery. Intra-arrest hypoglycaemia might be a marker of critical illness. Dextrose administration was not shown to improve outcomes of IHCA patients with intra-arrest BG level ≤ 150 mg/dl, indicating the need to develop new therapeutics other than dextrose administration for these patients.